2011
DOI: 10.3892/mmr.2011.712
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth of BG-1 ovarian cancer cells is promoted by di-n-butyl phthalate and hexabromocyclododecane via upregulation of the cyclin D and cyclin-dependent kinase-4 genes

Abstract: Abstract. Endocrine-disrupting chemicals (EDCs) are environmentally persistent exogenous compounds released from various industrial products such as plastics, pesticides, drugs, detergents and cosmetics. They can cause a variety of adverse effects to the reproductive, developmental, immune and nervous systems in humans and wildlife. Di-n-butyl phthalate (DBP) is the main compound of phthalates and is reported to inhibit estrogen receptor (ER)-mediated gene expression and to interfere with normal fetal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In addition to immune evasion mechanisms ( 36 , 142 , 145 ), they interfere with wide spectrum of cancer-related mechanisms ( 36 , 173 , 429 , 462–464 ). DEHP ( 472 ) is also an endocrine disruptor ( 466 , 467 ) that can impact multiple hallmarks such as immune evasion, resistance to cell death, evasion of antiproliferative signaling, sustained proliferative signaling and tumor-promoting inflammation ( 36 , 288 , 468 , 469 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to immune evasion mechanisms ( 36 , 142 , 145 ), they interfere with wide spectrum of cancer-related mechanisms ( 36 , 173 , 429 , 462–464 ). DEHP ( 472 ) is also an endocrine disruptor ( 466 , 467 ) that can impact multiple hallmarks such as immune evasion, resistance to cell death, evasion of antiproliferative signaling, sustained proliferative signaling and tumor-promoting inflammation ( 36 , 288 , 468 , 469 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al (2006) demonstrated increased gene expression for Cyclin B in cancerous cervical tissue from human subjects. Gene expression for Cyclin D and Cdk-4 has been shown to be up-regulated in BG-1 ovarian cancer cells following exposure to di-n-butyl phthalate and hexabromocyclododecane (another BFR) through putative estrogenic activity (Park et al 2012). In the present study, expression of Igf1 , the gene encoding growth factor IGF-1, increased in both sections of the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study, exposure to di-(2-ethylhexyl) phthalate at 500 and 2,000 mg/kg demonstrated ovarian toxicity through decreased progesterone and increased apoptosis in granulosa cells (23). Further, ovarian cancer cell lines have been found to increase cell proliferation and to up-regulate cell-cycle regulatory genes following treatment with di-n-butyl phthalate (24). We did not collect detailed information about specific products used in douching, so we are unable to estimate exposure to individual phthalates.…”
Section: Discussionmentioning
confidence: 99%